2019
DOI: 10.3390/ijms21010256
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrochalcone Derivatives from Populus balsamifera L. Buds for the Treatment of Psoriasis

Abstract: Psoriasis is a skin disorder characterized by epidermal hyperplasia, hyperkeratosis, and inflammation. The treatments currently available on the market only improve patients’ quality of life and are associated with undesirable side effects. Thus, research leading to the development of new, effective, and safer therapeutic agents is still relevant. Populus balsamifera L. buds were used traditionally by Native Americans to treat various skin pathologies such as eczema and psoriasis. In this study, the antipsoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
1
25
0
2
Order By: Relevance
“…RAW 264.7 cells are a well-established model for predicting the anti-inflammatory potential of drugs, since they easily increase NO production upon stimulation through incremental iNOS expression. This model has been widely used in the context of psoriasis [43,44] and was adopted in this study.…”
Section: Anti-inflammatory Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…RAW 264.7 cells are a well-established model for predicting the anti-inflammatory potential of drugs, since they easily increase NO production upon stimulation through incremental iNOS expression. This model has been widely used in the context of psoriasis [43,44] and was adopted in this study.…”
Section: Anti-inflammatory Potentialmentioning
confidence: 99%
“…HPLC-PDA recorded at 450 nm. Unidentified carotenoids (3, 5-8, 10-13, 15, 23, 25, 28, 31, 40-43), β-carotene oxygenated derivatives (9, 17, 34, 35), Lutein derivatives(14,16,19,22,24), Echinenone derivatives(30), Chlorophyll a derivatives(32,33,38), Unidentified Chlorophylls(44)(45)(46)(47), Zeaxanthin(21), Canthaxanthin(26), Chlorophyll a(36), Echinenone(37), all-trans β-Carotene (48), α-Carotene derivative (49), 13-cis-β-Carotene(50).…”
mentioning
confidence: 99%
“…The cited authors demonstrated that positive effects could be obtained with as little as 50 μg of astilbin. The use of antioxidative balsacones isolated from balsam poplar ( Populus balsamifera L) on human fibroblasts harvested from fragments of psoriatic skin reduced the cell growth rate and stabilised the expression of cells in involucrin and loricrin more effectively than methotrexate [ 150 ]. Local application of propolis, due to its content of flavonoids, helps to improve the condition of psoriatic skin by suppressing the activity of macrophages and production of ROS [ 151 ].…”
Section: External Application Of Antioxidants In Psoriasismentioning
confidence: 99%
“…Many parts of this tree, such as the buds, leaves, and bark, can be used as active ingredients for the pharmaceutical industry. In European traditional medicine, black poplar buds were generally recommended as a remedy in respiratory infections (cough, laryngitis, bronchitis, sore throat) and also in the treatment of dermatological problems (psoriasis), rheumatic inflammations, and hemorrhoids [ 17 ].…”
Section: Introductionmentioning
confidence: 99%